STUDI TINDAK PIDANA KORUPSI MENGENAI PENYUAPAN DI KEMENTERIAN SOSIAL REPUBLIK INDONESIA: Study Of Corruption Crimes Regarding Bribery In The Ministry Of Social Republic Of Indonesia - Indra Permana; Yenti Garnasih (Reformasi Hukum Trisakti, 2024)
Corruption is extraordinary crime, carried out in a structured, systematic and massive manner, has a broad impact at the national and international levels, and the regulations are fairly special, namely outside the Criminal Code, and the impact causes material and immaterial losses to society. One of the cases involved an Indonesian government agency, namely the Indonesian Ministry of Social Affairs, carried out by the Indonesian Minister of Social Affairs who served in 2019-2020. The problem is whether the actions carried out by the perpetrator have complied with Article 5 of Law Number 20 of 2001. The research method was carried out normatively with the nature of the research using analytical descriptive, the type of data used was secondary data, qualitative data analysis and drawing conclusions based on the method deductive logic. The results and discussion are examining whether the application, of the article is appropriate or not and the form of inclusion of the perpetrator. The conclusion is that the perpetrator should not be charged with Article 5 of Law Number 20 of 2001 because one of the elements contained in that article is not fulfilled or has not been legally and convincingly proven according to the law.